2022
DOI: 10.1002/ece3.8992
|View full text |Cite
|
Sign up to set email alerts
|

Thermobiological effects of temperature‐induced color variations inAglais urticae(Lepidoptera, Nymphalidae)

Abstract: Coloration of animals is important for camouflage, for social behavior, or for physiological fitness. This study investigates the color variation in adults of Aglais urticae obtained on subjecting some pre-imaginal stages to different temperature conditions and their thermobiological consequences. To investigate the evolutionary-ecological interactions of temperature and pigmentation in butterflies, caterpillars, and pupae of the small tortoiseshell,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Differences between species may change if we recorded steady state temperature, rather than heat gain. 42 Nonetheless, our study and these previous studies suggest that reflectance influences body temperature of intertidal gastropods in natural conditions.…”
Section: Discussionsupporting
confidence: 43%
“…Differences between species may change if we recorded steady state temperature, rather than heat gain. 42 Nonetheless, our study and these previous studies suggest that reflectance influences body temperature of intertidal gastropods in natural conditions.…”
Section: Discussionsupporting
confidence: 43%
“…It means that individuals were cryptic against most of the backgrounds, except for the two forementioned combinations. Studies with monarch butterflies showed that colder temperatures induce darker forms in caterpillars, while hotter regimes make them lighter (Davis et al 2005, Markl et al 2022), a phenom known as "Thermally melanism". Although we did not investigate the relationship between such variables and M. brevipennis, we believe that it is most likely to happen, as individuals were, indeed darker in the dry and colder seasons, and lighter in the wet season.…”
Section: Resultsmentioning
confidence: 99%